Oxford Picture Dictionary : English-Urdu - Parnwell, E. C.; Translated by Ahmad Faruqi Khwaja (Karachi Oxford University Press, 1990)
2,000 words presented by topic. Large, detailed pictures for most topics, with a numbered key linking the words with the illustrations. Alphabetical index which includes pronunciation. Accompanying Workbook, Wallcharts and OHP transparencies. Bilingual editions available
Include Color Illustration
Keywords: English language -- Picture dictionaries, English -- Picture dictionaries, Panjabi